2016
DOI: 10.1590/1809-4430-eng.agric.v36n6p1027-1036/2016
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Analysis Methods of Slope Stability for Different Geotechnical Classes Soil on Earth Dams

Abstract: The aim of this study was to evaluate the performance of less accurate analysis methods of slope stability, in order to reduce the number of operations used by the most accurate methods available in the literature. The study evaluated four methods for calculating slope stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…The simplified Bishop method, as one of the ultimate balance methods, is considered to be a "non-strict" method because it ignores the shear force between strips and does not strictly satisfy the equilibrium conditions. However, many scholars have found that the stability factors of slopes obtained by the improved Bishop method and the strict method are very close, which can be called the strict strip method [30][31][32]. The traditional simplified Bishop method is only suitable for the stability analysis of natural slope, but cannot be directly used to analyze the stability of a slope with a supporting structure.…”
Section: Stability Analysis Model Of Filled-slope Reinforced By Frame...mentioning
confidence: 99%
See 1 more Smart Citation
“…The simplified Bishop method, as one of the ultimate balance methods, is considered to be a "non-strict" method because it ignores the shear force between strips and does not strictly satisfy the equilibrium conditions. However, many scholars have found that the stability factors of slopes obtained by the improved Bishop method and the strict method are very close, which can be called the strict strip method [30][31][32]. The traditional simplified Bishop method is only suitable for the stability analysis of natural slope, but cannot be directly used to analyze the stability of a slope with a supporting structure.…”
Section: Stability Analysis Model Of Filled-slope Reinforced By Frame...mentioning
confidence: 99%
“…where t is the total number of layers of the prestressed anchor-plate; Tuf is the ultimate bearing capacity of the f-layer anchor-plate, which can be determined by Equation (31); αf is the angle between the tangent line and the horizontal direction at the intersection of the f-layer anchor-plate and the slip surface; φf is the internal friction angle of the soil at the intersection point of the f-layer anchor-plate and the slip surface; L is the total arc length of the slip surface. The force diagram of the soil strip considering the action of the supporting structure is shown in Figure 11, according to the Mohr-Coulomb criterion [30]:…”
Section: Stability Analysis In Thementioning
confidence: 99%
“…Despite the introduction of a new advanced method, the slice method is still the most well-known and widely used to estimate the SF [34]. Pereira et al [35] compared several methods of slope stability analysis and determined that the simplified Bishop, simplified Janbu, and Bishop methods have the optimum performance, with the correlation coefficient of 99% for the simplified Bishop. The authors still consider the limitation of the definition of the SF in traditional slice methods and do not introduce new concepts of the slice-wise SF and limit equilibrium method.…”
Section:  mentioning
confidence: 99%
“…U radu [20] dat je pregled numeričkih metoda stabilnosti klizišta, pri čemu je korišćena formulacija po metodi konačnih razlika (FDM -Finite Difference Method). Studija performansi nekoliko različitih metoda stabilnosti klizišta prikazana je u radu [27], dok su u radu [21] prikazane metode stabilosti klizišta, imajući u vidu deterministički pristup, teoriju pouzdanosti i optimizacije. Primena numeričkih metoda analize stabilnosti kosina u izmenjenoj serpentinskoj stenskoj masi prikazana je u radu [25], pri čemu su, između ostalog, korišćeni i sledeći parametri: geološ-ki indeks čvrstoće i deformabilnosti stenske mase, dok je kao kriterijum sloma primenjen Hoek Brown-ov kriterijum.…”
Section: Introductionunclassified
“…The paper [20] gives an overview of the numerical methods of landslide stability, using the Finite Difference Method (FDM) formulation. A study of the performances of several different landslide stability methods is presented in [27], while in [21] the methods of landslide stability are presented taking into account the deterministic approach, the theory of reliability and optimization. The use of numerical methods for analyzing the stability of slopes in the alternating serpentine rock mass was shown in [25], where, among other things, these parameters were used: the geological strength index and deformability of the rock mass, and for the criterion of failure Hoek Brown's criterion was applied.…”
Section: Introductionmentioning
confidence: 99%